2018
DOI: 10.1080/01443615.2018.1432578
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a vaginal suppository formulation of dill (Anethum graveolens) in comparison to clotrimazole vaginal tablet on the treatment of vulvovaginal candidiasis

Abstract: The goal of this study was to compare the effect of Anethum graveolens (dill) vaginal suppositories and 100 mg clotrimazole vaginal tablets on vulvovaginal Candidiasis. This study was a single centre, single-blind, randomised, placebo-controlled trial, in which 60 women with microbiology-confirmed vulvovaginal candidiasis were randomly assigned to dill and clotrimazole groups. At the end of the study, the estimated prevalence of leucorrhoea, burning, and itching was 23%, 23% and 20% in dill users, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, a recent study with a smaller sample size compared the efficacy of dill vaginal suppository and Clotrimazole vaginal tablet. The prevalence percentages of itching, leucorrhoea, burning, and positive cultures were 20%, 23.3%, 23.3%, and 10%, respectively for dill suppository, and 16.7%, 20%, 10%, and 13.3% for Clotrimazole tablet at the end of intervention without any significant differences (32). Bingxin et al studied the probable antifungal mechanism of dill seed essential oil and revealed its antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study with a smaller sample size compared the efficacy of dill vaginal suppository and Clotrimazole vaginal tablet. The prevalence percentages of itching, leucorrhoea, burning, and positive cultures were 20%, 23.3%, 23.3%, and 10%, respectively for dill suppository, and 16.7%, 20%, 10%, and 13.3% for Clotrimazole tablet at the end of intervention without any significant differences (32). Bingxin et al studied the probable antifungal mechanism of dill seed essential oil and revealed its antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitudes of improvement from dill were similar to those observed in children given the antibiotic metronidazole. Two trials investigated dill extracts as either a vaginal suppository 55 or vaginal cream 56 for the treatment of vulvovaginal candidiasis. Compared with baselines, these interventions significantly reduced clinical symptoms of infection, which were similar to the outcomes for subjects administered the antifungal agent clotrimazole.…”
Section: Effects Of Dill On Human Healthmentioning
confidence: 99%
“…Cinnamon also inhibits nitric oxide due to its cinnamaldehyde and has an anti-inflammatory effect (23). A study conducted in 2018 showed no difference in treatment results between the two groups of dill cream and clotrimazole (24).…”
Section: This Study Examined Oral Cinnamon Capsules On Candidal Vagin...mentioning
confidence: 99%